English Grammar Teaching in Translation Programmes: A Data-Driven Learning, Task-Based Approach (Ddl-Tb); [Enseñanza de Gramática Inglesa en Programas de Traducción: Aprendizaje Basado en Datos Enmarcado en Un Enfoque por Tareas (Abd-Et)] - Poblete-Bravo, J; Singer-Contreras, N (Pontificia Universidad Catolica de Chile, 2022)
Translator education in monolingual contexts presupposes that students should develop their translation and linguistic competence concurrently, which presents a series of pedagogical challenges. This evaluative descriptive study examines the use of data-driven learning in a task-based approach (DDL-TB) for teaching grammar in a Chilean translation programme. Such an approach implies the exploration of a corpus to find different patterns or linguistic phenomena. The paper presents the design and graduation of tasks and, later, examines the translation students’ and lecturer’s perspectives about the suitability of this approach for English grammar teaching. The students’ comments suggest that the approach allowed them to 1) reflect on the way they learn languages and 2) develop an active role in their formative process. The lecturer highlights that the approach aligns with the learning objectives of the course unit, allowing the course to be effectively ‘descriptive’. It is concluded that the narratives examined in this study indicate that an ABD-ET approach would be suitable for English grammar teaching in translation education. © 2022 Pontificia Universidad Catolica de Chile. All rights reserved.